2014
DOI: 10.3906/sag-1304-136
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical implications of P53, P63, and P73 protein in malignant tumor of the parotid gland

Abstract: Background/aim: To investigate the expression of P53, P63, and P73 proteins in malignant parotid gland tumors and adjacent nonneoplastic tissues and the association between the 3 proteins and their clinical characteristics. Materials and methods:A total of 40 pairs of paraffin-embedded malignant parotid gland tumors and adjacent nonneoplastic tissues were collected. We detected P53, P63, and P73 protein expression by immunohistochemistry. Statistical analysis was performed by using the chi-square test.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Similarly, Liu et al [8] also reported that TP73 was overexpressed in cervical cancer tissues compared with normal cervical tissues. In addition, high expression of TP73 was suggested in several kinds of human tumors such as breast cancer [15,16], esophageal cancer [17], thymic carcinoma [18], extrahepatic bile duct carcinoma [19], cholangiocellular carcinoma [20], hepatocellular carcinoma [21,22], gastric cancer [23,24], colorectal cancer [25–27], ovarian cancer [28], laryngeal cancer [29], parotid gland carcinoma [30], cutaneous melanoma [31] and retinoblastoma [32]. However, low TP73 expression was observed in bladder cancer and head and neck squamous cell carcinoma, compared to corresponding normal tissues [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al [8] also reported that TP73 was overexpressed in cervical cancer tissues compared with normal cervical tissues. In addition, high expression of TP73 was suggested in several kinds of human tumors such as breast cancer [15,16], esophageal cancer [17], thymic carcinoma [18], extrahepatic bile duct carcinoma [19], cholangiocellular carcinoma [20], hepatocellular carcinoma [21,22], gastric cancer [23,24], colorectal cancer [25–27], ovarian cancer [28], laryngeal cancer [29], parotid gland carcinoma [30], cutaneous melanoma [31] and retinoblastoma [32]. However, low TP73 expression was observed in bladder cancer and head and neck squamous cell carcinoma, compared to corresponding normal tissues [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the study and control groups were not obviously different in the clinical general data, according to the comparison between the two groups (P>0.05), protecting this experiment from the interference by some basic clinical indicators. The analysis of the relationship between the expression level of p73 in the peripheral blood and the clinicopathological features of WT revealed the differences of the p73 expression levels among patients with different tumor sizes, pathological types, lymph node metastasis, and treatment outcomes (P<0.05), suggesting the important role of p73 in the occurrence and development of WT (28). This study found that the expression level of p73 in the peripheral blood of the study group (4.04±0.79) was much higher than that of the control group (1.57±1.12), indicating the high concentration of p73 in the patients serum.…”
Section: Discussionmentioning
confidence: 99%
“…Each section was observed in 10 random fields under ×200 magnification (18). The score was calculated by adding the scores for intensity (weak=1, moderate=2, intense=3) and proportion (5%=1, 6–24%=2, 25–49%=3, 50–74%=4, ≥75%=5) of positively stained cells (19). Scores of ≥2 were considered positive.…”
Section: Methodsmentioning
confidence: 99%